Immunopharmacology and Inflammation (Springer International Publishing, 2018)
A comprehensive overview of the current research on inflammation and immunopharmacology, with particular attention to the use of anti-inflammatory drugs, this book discusses future trends in this area of pharmacological research. It addresses an audience with basic knowledge in the inflammatory process, immune system, and pharmacology. Immunopharmacology and Inflammation meets the needs of graduate students, junior and senior researchers and is useful as a source of the most current information for those already working in these fields. .